Update on the Treatment of Metastatic Squamous Non-Small Cell Lung Cancer in New Era of Personalized Medicine - Soldera, Sara Victoria; Leighl, Natasha B. (Frontiers in Oncology, 2017)
Despite advances in molecular characterization and lung cancer treatment in recent years, treatment options for patients diagnosed with squamous cell carcinoma of the lung (SCC) remain limited as actionable mutations are rarely detected in this subtype. This article reviews potential molecular targets and associated novel agents for the treatment of advanced SCC in the era of personalized medicine. Elements of various pathways including epidermal growth factor receptor (EGFR), PI3KCA, fibroblast growth factor receptor (FGFR), retinoblastoma (Rb1), cyclin-dependent kinases (CDK), discoidin domain receptor tyrosine kinase 2 (DDR2) and mesenchymal-to-epithelial transition (MET) may play pivotal roles in the development of SCC and are under investigation for drug development.